Analysis of Sexual Dimorphism Through Anthropometric Measurements of The Feet: A Literature Review and Measurement Methodology - Inayah, Rizqi Nurul (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze gender based on footprints from various ethnicities in the World. The method used is a literature study with data sources from various studies by identifying PICO (Population/Patient, Intervention, Comparison, Outcome). For Population: ethnicity in the world, Intervention: -, Comparison or comparison: footprint measurement, and Outcome or result: gender determination. Data collection was done by downloading literature from three search engines, namely Google Scholar, Sciencedirect, and PubMed. The results of this study show that anthropometric foot measurements can be effectively used to determine sex, with various studies showing significant sexual dimorphism in foot size between men and women. On average, men have greater foot length and width than women, which can be utilized for sex estimation with a high degree of accuracy. The diverse measurement methodologies, such as length, width and foot index measurements, reflect flexibility in adaptation based on different population contexts. This study also shows the importance of considering cultural and ethnic factors in anthropometric analysis, which can affect measurement results. The findings have practical applications in a variety of fields, including forensics and product design, and confirm that footprint dimensions can be a strong indicator of gender differentiation.